Impact of pruning severity, chicken manure, and foliar application of kare combi on productivity and quality of zaitouni grape cultivar (Vitis vinifera L.) - Shawkat Al-Atrushy; R. Ibrahim (Mesopotamia Journal of Agriculture)
This research aimed to study the effect of pruning severity, soil application of chicken manure, and foliar application of Kare Combi on productivity and quality of the Zaitouni grape (Vitis vinifera L.), during growing seasons 2021, using a Randomized Complete Design with three replications. Winter pruning with three levels (4, 6, and 8 buds.vine-1) was done in the 2nd week of march, chicken manure was added to the soil with three levels (0, 3, and 6 kg.vine-1), and foliar application of Care-combi with three concentration (0, 6 and 12 mg.L-1). The results showed that No of clusters, counterweight yield per vine as well as TSS, total sugar percentage, and Anthocyanin content, were increased significantly by pruning, chicken manure, and foliar application of kare-combi as compared with control, concerning the interaction, the best results were with the interaction of 4buds.cane-1+6 kg.vine-1 chicken manure+ 12 mg.L-1 Kare-combi for cluster’s weight, TSS % total sugar %, and anthocyanin content, while the best interaction for the number of clusters per vine and total yield per vine resulted from the interaction of 8 buds.cane-1+6 kg.vine-1 chicken manure+ 12 mg.L-1 Kare-combi.